Взаимодействие человека с родовым уровнем бытия с точки зрения сущего и должного - Макуха, Г.В. (Культура народов Причерноморья, 2014)
В статье исследуется проблема взаимодействия человека с другим человеком как родовым
существом, а так же отношение человека к роду (на уровне семьи, национальности, человечества) с
точки зрения сущего и должного; делается вывод о том, что в действительности (сущее) произошло
отчуждение человека от родового уровня бытия, что привело к нравственному кризису человечества и
угрозе его самоуничтожения в результате Третьей мировой войны; излагаются концептуальные
рекомендации по преобразованию сущего отношения человека к роду в должное. У статті досліджується проблема взаємодії людини з іншою людиною як родовою істотою,
а так само відношення людини до роду (на рівні сім'ї, національності, людства) з погляду сущого і
належного; робиться висновок про те, що насправді (суще) відбулося відчуження людини від родового
рівня буття, що привело до етичної кризи людства і загрози його самознищення в результаті Третьої
світової війни; висловлюються концептуальні рекомендації по перетворенню сущого вiдношення людини
до роду в належне. In the article examined the problem of co-operation of men with other man as family (rod) creature,
and similarly attitude of man toward family, rod (at the level of family, nationality, humanity) from point of pure
(real) and due (obligatory). The theoretical questions are examined in the first part of the article: 1) what is a
family (rod) level of life, 2) what is a rodocentrism as philosophical direction, 3) in what a specific of categories
«pure» («real») and «due» («obligatory»). In the second part of the article co-operating of men is examined by
other man as family (rod) creature from point of due (obligatory). In the third part of the article a conclusion is
done that in reality, in actual fact alienation of man happened from the family (rod) level of life (the display of
which it is been: terrorism, criminality, commercial egoism, mercenary attitude toward other people). All of it
resulted in the moral crisis of modern society and to the threat of Third world war. In fourth part of the article
conceptual recommendations are expounded on transformation of actual (real) co-operation of men with the
family (rod) level of life in due, obligatory co-operation. The use of these recommendations will result in
overcoming of moral crisis in society and will weaken the threat of self-destruction of humanity.